2017
DOI: 10.1177/1049732317730818
|View full text |Cite
|
Sign up to set email alerts
|

Dementia and Migration: Family Care Patterns Merging With Public Care Services

Abstract: This article focuses on cognitive impairment and dementia in the context of transnational migration. Based on data from focus group discussions and interviews, we conclude that to adjust to the needs of care within ethnic-minority communities, it is important to consider not only the availability of household and kin members but also the present understanding of obligation and reciprocity underlying the perception of care. Another important issue to realize is that caregivers, women in particular, might feel o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
94
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(109 citation statements)
references
References 33 publications
12
94
0
3
Order By: Relevance
“…This study is the first to consider in more detail the organization of family dementia care in Turkish, Pakistani, and Arabic speaking minority ethnic families in Denmark. As in previous studies in minority ethnic communities in Europe (Baghirathan et al, 2018;Berdai Chaouni & De Donder, 2018;Hossain et al, 2018;Naess & Moen, 2015;Parveen et al, 2017;Sagbakken, Spilker, & Ingebretsen, 2018;Sagbakken, Spilker, & Nielsen, 2018;van Wezel et al, 2016), we found a preference for keeping dementia care within the family with limited support from formal care services but more details about how this was managed by the families.…”
Section: Discussionsupporting
confidence: 82%
“…This study is the first to consider in more detail the organization of family dementia care in Turkish, Pakistani, and Arabic speaking minority ethnic families in Denmark. As in previous studies in minority ethnic communities in Europe (Baghirathan et al, 2018;Berdai Chaouni & De Donder, 2018;Hossain et al, 2018;Naess & Moen, 2015;Parveen et al, 2017;Sagbakken, Spilker, & Ingebretsen, 2018;Sagbakken, Spilker, & Nielsen, 2018;van Wezel et al, 2016), we found a preference for keeping dementia care within the family with limited support from formal care services but more details about how this was managed by the families.…”
Section: Discussionsupporting
confidence: 82%
“…In a survey of healthcare use in Europe, migrants showed higher rates of consumption than native-born across countries. This was true for both physician visits and hospital stays, which is compatible with an aging migrant population with health deterioration (Solé-Auró, Guillén, & Crimmins, 2012). Similar migrant healthcare consumption trajectories seem probable in Norway.…”
Section: Discussionsupporting
confidence: 63%
“…Moreover, according to Elstad (2016), the world region origin, reason for migration and duration of residence are important sources for variations in migrants' utilization of healthcare services. Solé-Auró et al (2012) suggest that the observed differences on migrants' access to and use of healthcare across countries requires further exploration of the cultural, political and financial features affecting the propensity for use of healthcare consumption. Therefore, migrant patients' experience of inclusion or exclusion from healthcare consumption needs to be addressed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They recommend, inter alia, that care providers should provide people with dementia and their relatives from ethnic minorities with speci c information and support services that take their cultural and linguistic background into account. Various studies also identify a large need for relief and support services for family caregivers of PwM with dementia, which must be oriented toward the individual and cultural needs of PwM and their relatives [26,[71][72][73][74][75]. In particular, the importance of mothertongue education about dementia and culturally sensitive treatment and support services [74], for example, through dementia hotlines [26], speci c counseling centers, or printed information materials [75], is emphasized.…”
Section: Discussionmentioning
confidence: 99%